PENGARUH DEBT TO EQUITY RATIO (DER), PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP RENTABILITAS EKONOMI PADA KOPERASI DI KOTA PALU - Syafitri, Prafita (Katalogis, 2016)
This research aims at exploring and analyzing 1)simultaneous effects of debt to equity ratio, cash turnover, and receivable turnover on economic profitability of cooperatives in Palu;Â 2) partial effect of debt to equity ratio towards economic profitability of cooperatives in Palu; 3) partial effect of cash turnover towards economic profitability of cooperatives in Palu; 4) partial effect of receivable turnover towards economic profitability of cooperatives in Palu. Its populuation icludes cooperatives in Palu between 2012-2014, a total of 264 cooperatives. Sampling technique used is purposive sampling that consists of cooperatives financial report in the form of balance sheet and income statement of 35 cooperatives in Palu within 3 years, 2012-2014. Therefore, the sample of this study is 105. Data collection techniques are documentation and library research. Data analysis is multiple linear regressions. The result show that debt to equity ratio, cash turnover, and receivable turnover simultaneously have positive and significant impact on economic profitability of cooperatives in Palu. Partially, debt to equity ratio has negative and significant impact on economic profitability of cooperatives in Palu, while cash turnover and receivable turnover have significant and positive impact on economic profitability of cooperatives in Palu.